Pengaruh Trust dan Penerimaan Teknologi terhadap Minat Konsumen dalam Pembelian Online (Studi kasus www.kaskus.us) - Adi Triatma; Fitriati Akmila (Sinergi: Kajian Bisnis dan Manajemen, 2012)
This study discusses the impact of trust and the acceptance of technology on consumer intention to purchase on line at www.kaskus.us. The focus of the study was to test whether privacy, security, trust, risk, perceived usefulness and ease of use influence student intention to purchase online. The sample taken are from Accounting Department Universitas Islam Indonesia students who purchase on line at the web site kaskus.us. The data were analyzed using multiple regression and SEM, then calculated with SmartPLS software. The results indicate that privacy and security have positive influence ontrust. Moreover, perceived usefulness and ease of use have positive and significant effect on interest in purchasing online. On the contrary trust have negative effect on the risk to buy online. Lastly, risk have negatively effect and not significant with the intention to purchase on line.Keywords:   security, privacy, trust, risk, perceived usefulness, perceived ease of use, intention, online purchase